Compras públicas sustentáveis: práticas que vem sendo adotadas pelos órgãos públicos - Pontarolli, Gerson Luiz (2021)
Sustainable national development was introduced through Law 12,349/2010, which is one of the basic principles that already exist in public bidding. In this way, the door was opened to a new reality, namely, the need for the State, among its various actions, to carry out its public purchases in a sustainable manner, meeting this new principle expressly provided for in current legislation, and to the others arising and that emerged as a real side effect of such a requirement. The research is qualitative and was carried out through the analysis of public notices, manuals or guides, existing policies and practices related to sustainable public procurement. For the sustainable analysis, entities from the federal, state and municipal spheres were chosen, opting for those that currently have greater availability of information on their portals. At the state level, the Paraná State Court of Justice and Companhia Paranaense de Energia – Copel were selected, at the municipal level the City Hall of Curitiba – URBS – Urbanização Curitiba and at the federal level the CGU – Comptroller General of the Union, the TRT 9 – Court Regional Labor Office of the 9th Region and IFRS – Federal Institute of Rio Grande do Sul. The documents were analyzed in the period 2017 to 2020. It was possible to identify compliance with the legislation for making purchases, however, when it comes to in order to comply with the items that refer to sustainable purchases, it is still necessary to improve the performance of the analyzed institutions, as well as greater encouragement and investment in scientific research related to the topic. It was also possible to develop a final checklist suggestion document, which can help the public administration when purchasing in a sustainable manner.